Arid1a deficiency sensitises pancreatic cancer to fatty acid synthase inhibition - Tzu‐Lei Kuo; Ya‐Chin Hou; Yan‐Shen Shan; Li‐Tzong Chen; Wen‐Chun Hung (Clinical and Translational Medicine, 2025)
Abstract Background Mutations in the AT‐rich interactive domain‐containing protein 1A (ARID1A) gene are frequently found in pancreatic cancer. However, the contribution of ARID1A inactivation to pancreatic tumorigenesis remains unclear. Previous work showed that depletion of Arid1a at early developmental stages induces metabolic disturbance and diabetes mellitus in mice. Methods and Results In this study, we generated a genetically engineered mouse model harboring both K‐ras mutation and Arid1a depletion (KAR mice). We found that the combination of these two genetic alterations induces pancreatic tumor formation. Compared to tumors in K‐ras and Tp53‐mutant mice (KPC mice), KAR tumors showed increased immune cell infiltration and reduced stromal activation. Transcriptomic analysis revealed significant upregulation of fatty acid metabolism and fatty acid synthase (FASN) in KAR tumors, with ARID1A directly regulating Fasn expression. Pharmacological inhibition of FASN reduced tumor cell viability and slowed tumor progression in vivo. Analysis of clinical datasets showed an inverse correlation between ARID1A and FASN expression, with high FASN levels predicting worse patient survival. Conclusion ARID1A deficiency promotes fatty acid metabolism to accelerate pancreatic tumorigenesis. FASN is a potential therapeutic target for ARID1A‐deficient pancreatic cancer.Mutations in AT‐rich interactive domain‐containing protein 1A (ARID1A) gene are frequently found in pancreatic cancer. However, the contribution of ARID1A inactivation to pancreatic tumourigenesis is not well‐characterised. Previously, we generated genetically engineered mice with specific depletion of Arid1a gene in the pancreas and found that depletion of Arid1a at early developmental stage induced metabolic disturbance and diabetes mellitus. In this study, we established a mouse model with K‐ras mutation and Arid1a depletion (KAR mice) in the pancreas and showed that the combination of these two genetic alterations induced pancreatic tumour formation. Compared to the tumours developed in mice with K‐ras mutation and Tp53 deficiency (KPC mice), KAR tumours exhibited increased immune cell infiltration and reduced stromal activation. Our results demonstrated a significant upregulation of fatty acid metabolism and fatty acid synthase (FASN) in the KAR tumours, with ARID1A directly regulating FASN expression. Inhibition of FASN by chemical inhibitor reduced tumour cell viability and slowed tumour progression in mice. Clinical data revealed a negative correlation between ARID1A expression and FASN, with high FASN levels associated with worse patient survival. Collectively, ARID1A deficiency upregulates fatty acid metabolism to accelerate pancreatic tumourigenesis and FASN is a potential therapeutic target for ARID1A‐deficient pancreatic cancer. Key points ARID1A mutations drive metabolic reprogramming in pancreatic cancer. Co‐occurrence of K‐ras mutation and Arid1a loss induces tumor formation with distinct immune microenvironment features. FASN is upregulated by ARID1A deficiency and its inhibition suppresses tumor growth. Targeting FASN may benefit patients with ARID1A‐deficient pancreatic cancer.